+0  
 
0
131
1
avatar

8(x + 5) − 2(x + 3) = 46

Guest Feb 18, 2017
 #1
avatar+87301 
0

8(x + 5) − 2(x + 3) = 46   simplify

 

8x + 40  - 2x - 6  = 46

 

6x + 34  = 46        subtract 34 from both sides

 

6x  = 12      divide by 6

 

x  = 2

 

 

cool cool cool

CPhill  Feb 18, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.